GIS Based Techno Economic Analysis for the Placement of Solar Powered Public Electric Vehicle Charging Stations in Denpasar City (ELKHA : Jurnal Teknik Elektro, 2026)
The rapid growth of electric vehicle (EV) adoption has increased the need for reliable public charging infrastructure in urban areas. In Indonesia, public charging stations are generally supplied by grid electricity (PLN), which may increase operational costs and emissions depending on the grid generation mix. Integrating solar photovoltaic (PV) into electric vehicle charging stations (EVCS) offers a cleaner option. however, it requires careful consideration of both spatial suitability and techno-economic feasibility at the planning stage. This study proposes an integrated GIS-based planning framework to identify priority areas for solar-powered public EV charging stations in Denpasar City, Indonesia. The approach combines GIS-based spatial suitability analysis and comparative techno-economic evaluation within a unified planning workflow. Spatial analysis is first applied to screen candidate zones based on accessibility, land use compatibility, population density, proximity to activity centers, and solar energy potential. Subsequently, a techno-economic assessment is conducted to evaluate the feasibility of renewable energy–powered EV charging systems in the shortlisted areas. The results indicate that central urban areas and commercial districts emerge as priority deployment zones, driven by high accessibility, stronger demand indicators, and favorable techno-economic characteristics. Mixed-use residential areas are identified as complementary options to expand service coverage, while peripheral and agricultural-dominated areas show limited suitability for early deployment. The proposed framework demonstrates how integrating spatial screening and techno-economic considerations within a planning-oriented workflow can support more informed decision-making for sustainable EV charging infrastructure development in urban environments.